Iron infusion in pregnancy and dental dysplasia in children—is there a link? - Amstad, Gabriela; Burkhardt, Tilo (Frontiers in Pediatrics, 2025)
Some intravenous iron preparations cause hypophosphatemia mediated by increased fibroblast growth factor 23. This hypophosphatemia lasts for weeks or months and, when administered to pregnant women, could affect fetal tooth mineralization, which starts in the fourth month of pregnancy. The fetus requires increased calcium and phosphate levels to meet the increased demand for bone and tooth mineralization, development, and growth. As bone mineralization is a priority, calcium and phosphate deficiency could be compensated for by impaired primary and permanent tooth mineralization. Since there is an association between calcium and phosphate deficiency and dental dysplasia in X-linked hypophosphatemic rickets, we hypothesize a possible similar association between hypophosphatemia induced by intravenous iron infusion and dental dysplasia. As the long-term clinical impact of maternal hypophosphatemia on the fetus has not yet been investigated, studies are required to examine the effects of maternal hypophosphatemia on the fetus. Close cooperation between obstetricians, pediatric dentists, and pediatricians is essential to study the effect of hypophosphatemia induced by intravenous iron infusion on the primary and permanent tooth maturation and mineralization, growth, and development in children.